2012
DOI: 10.1177/0269215512445396
|View full text |Cite
|
Sign up to set email alerts
|

Oral nutritional support of older (65 years+) medical and surgical patients after discharge from hospital: systematic review and meta-analysis of randomized controlled trials

Abstract: Although the evidence is limited, we suggest that oral nutritional support may be considered for older malnourished medical and surgical patients after discharge from hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 31 publications
2
64
0
3
Order By: Relevance
“…This is especially important in elderly patients 132 . Maintenance of enteral nutrition in home care (with home-based nutritional therapy) may contribute to increase nutritional intake after major operations 133 and prevent post-operative nutritional deterioration 134,135 .…”
Section: Howmentioning
confidence: 99%
“…This is especially important in elderly patients 132 . Maintenance of enteral nutrition in home care (with home-based nutritional therapy) may contribute to increase nutritional intake after major operations 133 and prevent post-operative nutritional deterioration 134,135 .…”
Section: Howmentioning
confidence: 99%
“…12,122 Some modifications may improve taste or texture tolerability but not affect swallow parameters. [134][135][136] Environmental modifications have proved successful in improving nutrition in residential care settings 137 and are adaptable to other settings. [134][135][136] Environmental modifications have proved successful in improving nutrition in residential care settings 137 and are adaptable to other settings.…”
Section: Interventionsmentioning
confidence: 99%
“…Studies have demonstrated that efforts on optimizing energy and protein intake at discharge and in the rehabilitation period after discharge are beneficial [11, pages 3299–3307], [3, pages 321–325], [14, pages 2239–2245], [13, pages 61–67], [15, pages 295–301], [4, pages 386–395], and [16]. A recent review found a positive effect on nutritional intake and/or nutritional status by nutritional intervention after discharge from hospital [17, pages 19–27]. These positive results were however only found in compliant patients [14, pages 2239–2245], and [3, pages 321–325].…”
Section: Introductionmentioning
confidence: 99%